A prospective observational study to compare postoperative complications and quality of life between patients undergoing umbilical hernia repair by open and laparoscopic methods - Subbiah, Venkatesh; Chandrabose, Karpagavel (International Surgery Journal, 2019)
Background: Surgery of umbilical hernias may be challenging due to the heterogeneity of presentation, multiple options for repair, and potential for complications, including infection and recurrence. Laparoscopic repair of a ventral hernia has gained the popularity in recent times for its advantage over the open surgery. Hence the study aimed to compare postoperative complications and quality of life between patients undergoing umbilical hernia repair by open and laparoscopic methods. Methods: The study was a prospective cohort study, conducted in the department of general surgery of a tertiary care teaching hospital. Patients undergoing umbilical hernia repair by the laparoscopic method and by open surgery were included in the study. The interoperative time, postoperative hospital stays, post-operative complications and quality of life between patients undergoing umbilical hernia repair by open and laparoscopic methods were assessed after the surgery. Results: A total of 64 people were included in the final analysis, with 32 subjects each in each group. 13 (40.6%) were males and 19 (59.4%) females in both the groups. The mean duration of open umbilical hernia surgery was 59.37±10.83, and it was only 46.87±12.74 for laparoscopic surgery. The difference was statistically significant (p<0.05). Post-operative period recovery time in days was significantly lesser for laparoscopic group. Pain score postoperative period was 6.52±0.87 for open surgery and 4.84±0.86 for laparoscopic surgery, and the difference was statically significant (p<0.05).The difference between individual Carolinas comfort scale scores and study group was statistically significant (p<0.001). Conclusions: Laparoscopic umbilical hernia leads to lesser operative time, early postoperative recovery and comparatively superior quality of life, as compared to open umbilical hernia repair.